Differential bone and vessel type formation at superior and dura periosteum during cranial bone defect repair - Yuankun Zhai; Zhuang Zhou; Xiaojie Xing; Mark Nuzzle; Xinping Zhang (Bone Research)
Abstract The cranial mesenchyme, originating from both neural crest and mesoderm, imparts remarkable regional specificity and complexity to postnatal calvarial tissue. While the distinct embryonic origins of the superior and dura periosteum of the cranial parietal bone have been described, the extent of their respective contributions to bone and vessel formation during adult bone defect repair remains superficially explored. Utilizing transgenic mouse models in conjunction with high-resolution multiphoton laser scanning microscopy (MPLSM), we have separately evaluated bone and vessel formation in the superior and dura periosteum before and after injury, as well as following intermittent treatment of recombinant peptide of human parathyroid hormone (rhPTH), Teriparatide. Our results show that new bone formation along the dura surface is three times greater than that along the superior periosteal surface following injury, regardless of Teriparatide treatment. Targeted deletion of PTH receptor PTH1R via SMA-CreER and Col 1a (2.3)-CreER results in selective reduction of bone formation, suggesting different progenitor cell pools in the adult superior and dura periosteum. Consistently, analyses of microvasculature show higher vessel density and better organized arterial-venous vessel network associated with a 10-fold more osteoblast clusters at dura periosteum as compared to superior periosteum. Intermittent rhPTH treatment further enhances the arterial vessel ratio at dura periosteum and type H vessel formation in cortical bone marrow space. Taken together, our study demonstrates a site-dependent coordinated osteogenic and angiogenic response, which is determined by regional osteogenic progenitor pool as well as the coupling blood vessel network at the site of cranial defect repair.